The Factors Affecting Customers’ Intention to Use Online Food Delivery Services: An Empirical Assessment - editor aibpm; Dwi Nita Aryani; Punjika Rathi; Xuan Lee Wen; Qian Lee Wei; Swee Yi Lee; Pei Xuan Lee; Dian Wahyu Agustin (Advances in Global Economics and Business Journal, 2022)
This paper aims to examine the factors that influence customer’s intention to use online food delivery services using the survey. Quantitative research methods, namely survey research, have been used. The study approach included a Google Forms-based online survey of 100 respondents, then analyzed using IBM SPSS Version 26. The data was collected from a fairly wide age range, occupational backgrounds, and income level. The results indicate that perceived convenience has the most statistically significant impact on the dependent variable (intention to use). Price and delivery time also significantly impact customers' intention to use OFD services. Perceived ease to use has little influence on the dependent variable. However, the attitude of the delivery person and the condition of the food delivered did not significantly influence customers’ intention to use OFD services.